An Approach to Improving Student Success in Science, Technology, Engineering, and Mathematics (STEM) Career Pathways - Oppenheimer, Steven B. (Ethn Dis, 2020)
In this article, we report on an 11-year study that explores approaches to improve student success in college by a five-week summer program in Mathematics and Language Arts for entering freshmen. To recruit students into the program, we invited students accepted at the university and listed as underrepresented and economically disadvantaged (Pell-eligible) by the Office of Institutional Research at California State University, Northridge. The program consisted of all-day Math and English enhancement in mixed ability groups. Results of this program examining Math and English performance at California State University, Northridge showed that students completing the summer programs during the 11-year study period had improved pass rates in Math and English at California State University, Northridge compared with students in a control group who did not participate in the summer program. The results show that intensive pre-college enhancement for entering freshmen can improve student success in college. Student graduation data from the early cohorts (2010, 2011, 2012) were obtained from Institutional Research. The summary results showed that students from the accepted/attending group had substantially increased GPAs and graduation rates, essentially closing the achievement gap. Increased interest in biomedical research careers was also developed by the program, as demonstrated by a five-fold number of summer enrichment participants entering the PhD, MARC (Minority Access to Research Careers) and RISE (Research Initiative for Scientific Enhancement) programs than students who did not attend summer enrichment.